Charitable Giving and "Excessive" Fundraising - Rose-Ackerman, Susan (Quarterly Journal of Economics, 1982)
Recently, some charities have been attacked for spending an â€œexcessiveâ€ portion of their resources on fundraising. This paper shows how competition for donations can push fundraising shares to high levels even when donors dislike charities that spend a large portion of receipts on fundraising. It also considers a case in which donors take account of the productivity of fundraising in generating gifts from others. In the light of the models developed in the paper, a variety of regulatory strategies are assessed from the dissemination of information to the establishment of a federated fund drive.